2013
DOI: 10.1186/1471-244x-13-53
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among inmates at the Eldoret prison in Western Kenya

Abstract: BackgroundCriminal activity and social problems are recognized as important outcomes of substance use and abuse. Little research has been carried out on substance use among prison inmates in Kenya. General population surveys that have examined drug use usually omit this ‘hidden’ population which may offer insight into drug related morbidity and invaluable preventive measures. This study is set out to determine the lifetime prevalence and factors associated with substance use, including the most frequently used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
50
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 25 publications
15
50
4
Order By: Relevance
“…Substance use in the past month (mostly cannabis or alcohol) has been reported by about 5% of detainees in Nigeria 88 and Kenya. 89 In a South African study 90 in which urine testing was done, either cannabis or methaqualone was detected among 45% of detainees at the time of police arrest. Although anecdotal reports describe the use of injection drugs in sub-Saharan African prisons, the frequency is unknown, but appears low.…”
Section: Tools Approaches and Structural Interventions To Preventiomentioning
confidence: 99%
See 1 more Smart Citation
“…Substance use in the past month (mostly cannabis or alcohol) has been reported by about 5% of detainees in Nigeria 88 and Kenya. 89 In a South African study 90 in which urine testing was done, either cannabis or methaqualone was detected among 45% of detainees at the time of police arrest. Although anecdotal reports describe the use of injection drugs in sub-Saharan African prisons, the frequency is unknown, but appears low.…”
Section: Tools Approaches and Structural Interventions To Preventiomentioning
confidence: 99%
“…Although anecdotal reports describe the use of injection drugs in sub-Saharan African prisons, the frequency is unknown, but appears low. 89 Depressive and anxiety disorders have been reported in a large proportion of detainees in several studies. 91,92 Despite the probable burden of these comorbidities, we identified only one description of mental health activities (in Malawi) 93 and one drug harm-reduction programme (in Mauritius) in prisons.…”
Section: Tools Approaches and Structural Interventions To Preventiomentioning
confidence: 99%
“…In addition, alcohol use has been reported to be associated with intimate partner violence [10]. One of the reasons why people use substance is to increase their confidence to commit crime [11]. In support of this, one study found that 10% of homicide offenders claimed that the offense took place while they were under the influence of a substance [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the prevalence of substance use disorder (SUD) among prisoners before imprisonment was higher than both from use in prison and use in the general population, which may indicate association between crime and substance use. Studies in prisoners have shown that prevalence ranged from 50 to 88% for general substance use and 13 to 86% for AUD before imprisonment [11,12,16,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. A recent systematic review of about 24 studies from 10 different countries reported prevalence of AUD ranging from 16 to 51% among newly incarcerated male prisoners, with a pooled prevalence of 26% [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation